Cyberculture and Digital Communication Anthrobological configuration of the political - Cuadra, Álvaro (Re-presentaciones: Periodismo, comunicación y sociedad, 2023)
The purpose of this article is to situate the new configuration of the political in relation to the cultural mutations derived from digital technological development and a new episteme, Computer Mediated Communication (CMC). The new modalities of “algorithmic governmentality” not only concern new administration and government strategies but, from a critical perspective, represent the advent of a new type of society, hyper-control societies. This is the unprecedented anthrobological configuration of the political in our days, a hybrid condition in which Artificial Intelligence must coexist with human intelligence.
Keywords: Cyberculture; CMC; Algorithmic governmentality; Hyper-control Society